Carcinoma of unknown primary abuts left clavicle: Case report and review of the literature. (2020) - Geropoulos, Georgios; Mitsos, Sofoklis; Lampridis, Savvas; Hayward, Martin; Scarci, Marco; Panagiotopoulos, Nikolaos
Highlights: Carcinoma of unknown primary clinical manifestations usually associated with head and neck region. Painless cervical Lymphadenopathy is the most common symptom of the disease. Laboratory tests usually do not identify the primary disease. Limited data exists about management and the role of surgery in carcinoma of unknown primary if a single neck mass exists without evidence of lymph node implication. Abstract: Introduction: Carcinoma of unknown primary is a well-recognized clinical syndrome which accounts for the 3–5% of all the malignancies. Patients with carcinoma of unknown primary usually present with late stage disease without having identified the primary source of the tumour despite an extensive diagnostic work-up. Presentation of case: A 60 years old male presented to the clinic complaining of a neck mass to the left lateral neck. Patient's history was unremarkable without evidence of any malignant disease. Clinical and radiological examination revealed a cystic mass extending from the lower one third of the neck to the left clavicle causing periostal reaction. Mass biopsy and PET-CT was unspecific for the primary origin of the mass. However in the context of tumour immunohistochemistry, HPV status, neck location and basaloid cell differentiation, the tumour mass was considered as carcinoma of unknown primary with possible oropharyngeal primary location. The patient underwent surgical resection of the mass, left clavicle and the first rib. One year after the operation the patient is disease free. Discussion: Although CUP usually presents with cervical lyphadenopathy, in our case there was no evidence of lymph node tissue infiltration in the neck region. Surgical resection of the mass showed that the location was extending within the cervical soft tissues and upper thorax. Taking into consideration the absence of lymphadenopathy this is an uncommon location of carcinoma of unknown primary in the neck. Conclusion: This is an uncommon location of CUP with possible implications in survival and management.